Sistematización de la práctica pedagógica I y II, realizada con los estudiantes de grado 4° del Colegio Paulo VI en el año 2021 - Lagos Acosta, Daniela (Universidad Antonio Nariño, 2022)
The purpose of this degree project is to collect, analyse and comment on the process experienced in the pedagogical practices I and II of the year 2021, at the Paulo VI school in the city of Bogota; Through it, the reconstruction and rediscovery of everything experienced in the formative process, exposing as a starting point the skills and difficulties of motor control and attention management presented by students between 9-11 years old during the development of classes, allowing from a deep analysis, to create various methodologies, strategies or work tools from the game, to help improve these motor and attention needs in students